RELATIONSHIP BETWEEN THE LEVEL OF EDUCATION EMPLOYEES EMPLOYEES AND ACHIEVEMENT IN KPMB IN SURABAYA - Anam, Chairul (Entrepreneur, 2012)
Abstract Enduring polemic on the relationship between education and ketenagakarjaan is a specific for developing countries. Because in the early stages of development these countries, the growth of industry and the private sector is still limited, then the labor problems embraced by the education sector. Thus education is responsible for the quality of training and employment, or in other words by themselves the problem of unemployment is the responsibility of educational institutions. In line with pembengunan countries that then the government sector or formal sector is a container holding a graduate education system, however, in line with its speed of development and development results, the government sector the longer experience boredom, while the private sector can not be met by the educational system that exist. In addressing the gap between the education system with the demands of labor, need to be reformulated duties and responsibilities of each sector. If not the case in each sector will allege that the other sectors did not meet their own needs, while the education sector be the butt of the lack of skills of the workforce required to meet. Keywords: Level Of Education, Work And Achievement Abstrak Polemik abadi tentang hubungan antara pendidikan dan ketenagakarjaan adalah khusus untuk negara-negara berkembang. Karena dalam tahap awal pengembangan negara ini, pertumbuhan industri dan sektor swasta masih terbatas, maka masalah ketenagakerjaan yang dianut oleh sektor pendidikan. Dengan demikian pendidikan bertanggung jawab atas kualitas pelatihan dan pekerjaan, atau dengan kata lain sendiri masalah pengangguran merupakan tanggung jawab lembaga pendidikan. Sejalan dengan negara-negara pembengunan yang kemudian sektor pemerintah atau sektor formal adalah wadah memegang sistem pendidikan pascasarjana, namun, sejalan dengan lajunya pembangunan dan pengembangan hasil, sektor pemerintah lagi pengalaman kebosanan, sementara sektor swasta tidak bisa dipenuhi oleh sistem pendidikan yang ada. Dalam mengatasi kesenjangan antara sistem pendidikan dengan tuntutan kerja, harus tugas dan tanggung jawab masing-masing sektor dirumuskan. Jika tidak terjadi di masing-masing sektor akan menyatakan bahwa sektor-sektor lain tidak memenuhi kebutuhan mereka sendiri, sedangkan sektor pendidikan menjadi bulan-bulanan kurangnya keterampilan tenaga kerja yang diperlukan untuk memenuhi. Kata kunci: Tingkat Pendidikan, Kerja Dan Prestasi